Financing Strategies to Facilitate Access to High-Cost Anticancer Drugs: A Systematic Review of the Literature - Chanthawat Patikorn; Suthira Taychakhoonavudh; Rungpetch Sakulbumrungsil; Dennis Ross-Degnan; Puree Anantachoti (Kerman University of Medical Sciences, 2022)
Background  Each country manages access to anticancer drugs differently due to variations in the structure and financing of the health system, but a summary of the various strategies used is absent. This study aimed to review and summarize financing strategies implemented across countries to facilitate access to high-cost anticancer drugs. Methods  We conducted a systematic review of articles referenced in PubMed, Embase, and Web of Science through May 12, 2021. Articles published in the English language from 2000 that describe strategies implemented in different countries to facilitate access to high-cost anticancer drugs were included. Letters, news articles, and proposed strategies were excluded. Quality assessment was not performed as we aimed to summarize the strategies. Data were analyzed by thematic analysis. A review protocol was registered at PROSPERO (CRD42018068616).Results  The review included 204 studies from 176 countries. Three themes of financing strategies were identified: (1) Basic pharmaceutical reimbursement and pricing policies, (2) Alternative funding strategies specific to high-cost drugs, and (3) Financial assistance for individual patients. Access in most countries depends mainly on basic pharmaceutical reimbursement policies (165 of 176 countries). Apart from that, high-income countries (HICs) tended to use funding strategies targeting high-cost drugs (72% of HICs vs 0%-24% of the rest), such as managed entry agreements (MEAs) or dedicated funds for high-cost drugs. In contrast, lower-income countries tended to implement financial assistance programs for cancer patients as a tool to increase access (32% of HICs vs 62%-79% of the rest).Conclusion  Many countries have implemented a combination of strategies to increase access to high-cost anticancer drugs. Most low- and middle-income countries utilized placement of anticancer drugs on a national list of essential medicines and patient assistance programs (PAPs) to facilitate access, while many HICs implemented a broader range of strategies.